2021
DOI: 10.1152/japplphysiol.00382.2020
|View full text |Cite
|
Sign up to set email alerts
|

No renal dysfunction or salt and water retention in acute mountain sickness at 4,559 m among young resting males after passive ascent

Abstract: Purpose: This study examined the role and function of the kidney at high altitude in relation to fluid balance and the development of acute mountain sickness (AMS), avoiding confounders that have contributed to conflicting results in previous studies. Methods: We examined 18 healthy male volunteers (18 - 40 years) not acclimatized to high altitude while on a controlled diet and resting recumbently for 24 h at Lausanne (altitude: 560 m) followed by a period of 44 hours after reaching the Regina Margherita hut (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
2
2
1
Order By: Relevance
“…Equally, the initial decrease in PA within the first 6 h was not apparent after 12 h of HH exposure and overall TBW remained unchanged after 4 days of continuous HH exposure. Interestingly, this observation is consistent with previous reports showing that AMS is not associated with changes in TBW [45].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Equally, the initial decrease in PA within the first 6 h was not apparent after 12 h of HH exposure and overall TBW remained unchanged after 4 days of continuous HH exposure. Interestingly, this observation is consistent with previous reports showing that AMS is not associated with changes in TBW [45].…”
Section: Discussionsupporting
confidence: 93%
“…This may be of clinical importance when comparing hydration status under HH conditions to corresponding sea level values throughout the day. Moreover, changes in body hydration have been previously reported to be a risk factor in the development of acute mountain sickness (AMS) [9,[36][37][38][39][40][41][42][43][44], even though contrasting data exist [45]. Accordingly, we aimed to assess whether circadian oscillation in TBW dynamics, as determined by BIVA, are influenced by prolonged exposure to HH conditions corresponding to 3500 m. In addition, we intended to investigate whether it would be possible to connect measurable changes in TBW during a 4-day HH sojourn to AMS diagnoses or any singular AMS-related symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Loeppky et al ( 10 ) in their study found indications for a similar biphasic response to a more severe HH, at least in subjects who tolerated the exposure well; however, in that study, water intake was adjusted to urine output, which made the interpretation more difficult than in the current setting. A short-lived diuresis increase within 1 h after arrival at 4,559 m altitude was also reported in a study by Biollaz et al ( 31 ), although the authors attributed this phenomenon to the excitement associated with the passive ascent by helicopter. The acute increase in urine flow in HH could have been mediated by the reduction in circulating aldosterone that was observed on M1 (even though it did not quite reach statistical significance).…”
Section: Discussionsupporting
confidence: 74%
“…What remains unclear is the fate of these proteins. Although Biollaz et al ( 31 ) in their study recently reported ascent to 4,559-m altitude to induce mild microalbuminuria in subjects confined to bedrest, urinary protein excretion was identical between the sojourns in the current study. Transvascular protein escape has been suggested to occur as hypoxia-induced inflammation ( 11 , 12 ) and/or endothelial glycocalyx shedding increase vascular permeability for albumin ( 21 ), but the unchanged inflammatory markers and inconsistent changes in markers for glycocalyx shedding in our study do not support these explanations.…”
Section: Discussioncontrasting
confidence: 68%
“…Since ANP exerts an inhibitory effect on aldosterone synthesis, vasopressin release and tubular sodium reabsorption, ANP was thought to contribute to body water changes at altitude (43). Yet, recent data demonstrate that body water is barely affected by hypobaric hypoxia (8,36). The mechanism underlying the decrease in ANP was unclear, but the reduction in PaO 2 , which persists throughout hypoxic exposure despite partial recovery by ventilatory acclimatization (9), seemed a plausible candidate.…”
Section: Discussionmentioning
confidence: 99%